Site‒specific IR spectroscopy and molecular modelling combined towards solving transmembrane protein structure. Issue 1 (2005) - Kukol Kukol, Andreas Andreas
Abstract : Membrane protein structures are underrepresented in structural databases despite their abundance and biomedical importance. This review focuses on the novel method of site-specific infrared dichroism (SSID) combined with constraint molecular dynamics simulation, which has recently emerged as a powerful method to obtain structures of transmembrane α-helical bundles. The theory of SSID including its latest developments is reviewed with the aim to encourage widespread application of this method. This is followed by an outline of the conformational search using experimentally constraint molecular dynamics simulations. Finally a critical evaluation of recent applications, namely the Influenza M2 proton channel, the vpu ion channel of HIV-1 and the MHC-class II associated invariant chain, is conducted.